2019
DOI: 10.1027/1015-5759/a000407
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Grit

Abstract: Abstract. The construct grit originates from positive psychology and describes an individual’s tendency to persistently pursue long-term goals despite challenges or obstacles. Previous research has shown that domain-general grit is a predictor of educational and vocational success. The present research aimed to establish and validate a German version of the Short Grit Scale by Duckworth and Quinn (2009) , named the BISS-8 ( Beharrlichkeit and Beständiges Intere sse) Scale, and to test for the domain specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
0
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 32 publications
(64 reference statements)
9
94
0
12
Order By: Relevance
“…These results are similar to those found by Duckworth and Quinn (2009), who obtained better fit indexes for the short version than for the long one. Also, several studies have found better indices for the grit structure with two related factors in both long and short versions (e.g., Abuhassàn & Bates, 2015;Datu et al, 2016;Lenz et al, 2018;Nishikawa et al, 2015;Schmidt et al, 2017;Sulla et al, 2018). In addition, the fit indexes found in the scale adapted to the Mexican context also coincide with those found by Abuhassàn and Bates (2015) and Datu et al (2016) who obtained adequate fit for two factors with six items each.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These results are similar to those found by Duckworth and Quinn (2009), who obtained better fit indexes for the short version than for the long one. Also, several studies have found better indices for the grit structure with two related factors in both long and short versions (e.g., Abuhassàn & Bates, 2015;Datu et al, 2016;Lenz et al, 2018;Nishikawa et al, 2015;Schmidt et al, 2017;Sulla et al, 2018). In addition, the fit indexes found in the scale adapted to the Mexican context also coincide with those found by Abuhassàn and Bates (2015) and Datu et al (2016) who obtained adequate fit for two factors with six items each.…”
Section: Discussionsupporting
confidence: 62%
“…Since the design of the Grit Scale, several adaptation and validity studies providing evidence of a bifactorial structure of the scale have been carried out across different cultural contexts such as Russia, Japan, Britain, Germany, Italy, The Philippines, China and Ghana among others (e.g., Abuhassàn & Bates, 2015;Datu, Valdez, & King, 2016;Lenz, Watson, Luo, Norris, & Nkyvi, 2018;Muenks, Wigfield, Yang, & O'Neal, 2017;Nishikawa, Okugami, & Amemiya, 2015;Schmidt, Fleckenstein, Retelsdorf, Eskreis-Winkler, & Möller, 2017;Sulla, Renati, Bonfiglio, & Rollo, 2018;Tyumeneva, Kuzmina, & Kardanova, 2014;Wang et al, 2017). However, Datu, Yuen and Chen (2017) validated a triarchic model of grit, where adaptability to the situation was an emergent factor for Grit assessment in Philippine culture, since non-significant results were found for the consistency of interest.…”
mentioning
confidence: 99%
“…Scores were averaged, and higher scores indicated greater perseverance. The Grit-S boasts acceptable psychometric properties (Duckworth & Quinn, 2009;Schmidt, Fleckenstein, Retelsdorf, Eskreis-Winkler, & Möller, 2017), and in the present study the internal reliability was .74.…”
Section: Self-reported Perseverancesupporting
confidence: 58%
“…Along similar lines, the review identified grit as a protective factor against gaming addiction (Borzikowsky and Bernhardt 2018) and disinhibition as a predictor factor for gaming addiction (Laier et al 2018). The Bgrit^personality trait is described as being persistent in pursuit of long-term goals despite obstacles (Schmidt et al 2017), and the disinhibition trait is associated with irresponsibility, impulsivity, and distractibility (Trull 2012). While higher grit (Eskreis-Winkler et al 2014) and lower disinhibition trait scores serve as a significant predictor factor for achievement, these patterns were identified as a protective factor against gaming addiction.…”
Section: Discussionmentioning
confidence: 95%